Revisit intention of rural tourism among local tourist in Kelantan - Nurulhuda Mohamad Syarif; Gabriel Foong Le Xuen; Aishah Abdul Jala; Nur Afif Putra Abdul Razak (2021)
This research observes the relationship of revisit intention of rural tourism among local tourist in Kelantan in 3 aspects which is customer satisfaction, price and destination image. The objectives of this research is firstly to investigate the relationship of customer satisfaction with revisit intention to rural tourism among local tourist in Kelantan.Secondly, this is to identify the relationship between the price and revisit intention to ruraltourism among local tourist in Kelantan and thirdly is to determine the relationship of destination image with revisit intention of rural tourism among local tourist in Kelantan. From 300 local tourists from Kelantan have been targeted to be the respondent and fortunately the total of 387 respondents has successfully answered the investigation through online survey which is questionnaire. The Statistical Package for Social Science(SPSS) was used in order to evaluate the data collection. The function of SPSS is to statethe whole statistical analysis process which is to plan, to collect the data, report for the best decision making and also performance. Then, the result shows that the strength of the association for revisit intention which is customer satisfaction, price and destination image was a very good level. Through this research we can comprehend about the revisit intention of rural tourism among local tourist in Kelantan.